Overcoming the conflict of jurisdiction in cybercrime - Khalifa, Abdelmonem Mohamed Magdy (AUC Knowledge Fountain, 2020)
This study explores the different approaches to managing the conflict of criminal jurisdiction over cybercrime with the aim of comparing the advantages and disadvantages of each approach. It argues that the most effective solution to this dilemma is to determine certain factors to be considered and evaluated by a body established for such a purpose or by the concerned states themselves in order to decide which country will take the exclusive competence over the cybercrime in accordance with the facts of each individual case and taking into account the characteristics of cybercrime. Establishment of these factors should reflect the interests of the different stakeholders related to cybercrime that include like other crimes the interest of victim(s), criminal(s), and concerned states. As long as it is accepted internationally that the jurisdiction over cybercrime can be established based on territory, active and passive personality, as well as the protective principles, the suggested factors should also include the interests of the state where the crime is committed, the state of the offender's nationality, the state of the victim's nationality, and the state whose vital interests have been affected by the crime. In addition, these factors should contain the interest of criminal proceedings as it is a must to achieve the interests of all the stakeholders. In my opinion, these factors should not be given equal weight as many factors are more relevant than others in light of the cybercrime particularities and the decision in this regard should be reached on the basis of an aggregate balance of all these factors.